Child-level evaluation of a web-based intervention to improve dietary guideline implementation in childcare centers: a cluster-randomized controlled trial. Issue 4 (24th February 2020) - Yoong, Sze Lin; Grady, Alice; Wiggers, John H; Stacey, Fiona G; Rissel, Chris; Flood, Victoria; Finch, Meghan; Wyse, Rebecca; Sutherland, Rachel; Salajan, David; O'Rourke, Ruby; Lecathelinais, Christophe; et al.
ABSTRACT: Background: Although it is recommended that childcare centers provide foods consistent with dietary guidelines, the impact of implementing sector-specific guidelines on child outcomes is largely unknown. Objectives: This study aims to examine the impact of a web-based program and support to implement dietary guidelines in childcare centers on children's 1 ) diet; 2 ) BMI z scores; and 3 ) child health-related quality of life (HRQoL). Methods: This study was a cluster-randomized controlled trial utilizing a Type-3 Hybrid implementation-effectiveness design conducted between October 2016 and March 2018. This study reports on child outcomes. Fifty-four childcare centers in New South Wales, Australia were randomly assigned to the intervention (a web-based menu-planning tool and support) or control group (usual care). The intervention was designed to address barriers and enablers to dietary guideline implementation according to the Theoretical Domains Framework. A quota of 35 consenting childcare centers undertook child-level evaluation of dietary intake where 522 parents consented to completing ≥1 component of data collection for their child. Child consumption of core and discretionary (unhealthy) foods while in care was assessed via dietary observations by blinded research assistants, childcare diet quality was assessed via educator-completed questionnaires, BMI z scores were assessed via measured weight and height, and child HRQoL was assessed via parent report at baseline and 12-mo follow-up. Results: There was a significant increase in mean child consumption of fruit (0.39 servings; 95% CI: 0.12, 0.65 servings) and dairy foods (0.38 servings; 95% CI: 0.19, 0.57 servings) and a significant reduction in consumption of discretionary foods (−0.40 servings; 95% CI: −0.64, −0.16 servings) in care in the intervention group, relative to control at 12-mo follow-up. No significant differences were observed in diet quality, BMI z scores, or HRQoL. Conclusions: A web-based intervention to support planning of childcare menus consistent with dietary guidelines can improve child consumption of healthier foods in daycare. This trial was registered at www.anzctr.org.au as ACTRN12616000974404.